2016
DOI: 10.1097/id.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Screw Loosening With Prefabricated Abutments and Customized CAD/CAM Abutments

Abstract: With precise control of CAD/CAM abutments, good screw joint stability can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…Tzannas et al [26] reported that the removal torque is 85 up to 90% of tightening torque. However, Paek et al [14] reported that there was no significant difference among initial tightening torque first or second removal torque. Their results may be attributed to the employment of two different devices for screw tightening in their study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tzannas et al [26] reported that the removal torque is 85 up to 90% of tightening torque. However, Paek et al [14] reported that there was no significant difference among initial tightening torque first or second removal torque. Their results may be attributed to the employment of two different devices for screw tightening in their study.…”
Section: Discussionmentioning
confidence: 97%
“…A study examined the stability of implant protheses with stock abutment, cast gold abutment, and milled custom abutment, and reported that the type of the abutment did not possess a significant influence on screw loosening after dynamic loading [13]. Another study showed good screw joint stability for stock and custom titanium abutments after cyclic loading [14].…”
Section: Introductionmentioning
confidence: 99%
“…CAD/CAM abutments seem to achieve adequate stability in the screw joint and offer a viable treatment option for single tooth implants . Kim et al suggested that, even though there are no significant differences on short‐term screw loosening between CAD/CAM abutments and prefabricated or gold cast abutments, CAD/CAM custom abutments may present higher incidence of screw loosening than the other abutments after dynamic loading .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, metal abutments are most often used, although the zirconia prosthetic abutments of high strength can be considered as an equally favorable option in clinical practice, [45][46][47][48] On the other hand, Cavusoglu et al suggested that the interface of zirconium abutment and titanium implants may be susceptible to wear of the abutment and deformation of the implant neck. 49 CAD/CAM abutments seem to achieve adequate stability in the screw joint 50 and offer a viable treatment option for single tooth implants. 51 Kim et al suggested that, even though there are no significant differences on short-term screw loosening between CAD/CAM abutments and prefabricated or gold cast abutments, CAD/CAM custom abutments may present higher incidence of screw loosening than the other abutments after dynamic loading.…”
Section: Materials Of the Prosthetic Abutmentmentioning
confidence: 99%
“…Many studies have been performed to overcome these complications through a series of stress analyses, including a finite element analysis (FEA). 7 8 9 10 11 12 13 14 15 16 17 18 19 20 …”
Section: Introductionmentioning
confidence: 99%